Technology Acceptance: Theories and Applications in Digital Tech - Mohd Shafie Rosli,; Saleh, Nor Shela; Azlah Md. Ali,; Suaibah Abu Bakar,; Sultan Hammad Alshammari, (Human Sustainability Procedia, 2021)
Digital tech or also known as digital technology is a daily driver of mankind. As time evolved, the usage of this technology become multiplex in nature. The acceptance of the technology introduced and the factors that influence the decision to or not to adopt technology become crucial. The situation motivates this research to identify suitable theoretical frameworks to study the human acceptance of digital tech. Bibliographic study via the partial adoption of narrative review and bibliographic coupling had led to Technology Acceptance Model and Unified Theory of Acceptance and Usage of Technology as suitable theories for understanding human acceptance of digital tech. Several other theories: Theory of Planned Behaviour, Theory of Reasoned Action, Theory of Planned Behaviour, Innovation Diffusion Theory and Social Cognitive Theory are also suitable for understanding technology acceptance in digital technology.